Comparative effectiveness of venous thromboembolism prophylaxis options for the patient undergoing total hip and knee replacement: a network meta‐analysis. (19th January 2017) - Kapoor, A.; Ellis, A.; Shaffer, N.; Gurwitz, J.; Chandramohan, A.; Saulino, J.; Ishak, A.; Okubanjo, T.; Michota, F.; Hylek, E.; Trikalinos, T. A
Abstract : Essentials Despite trial data, guidelines have not endorsed direct oral Xa inhibitors above other options. We provide profiles of venous thromboembolism and hemorrhage risk for 12 options. Direct oral Xa inhibitors had a favorable profile compared with low‐molecular‐weight heparin. Other options did not have favorable profiles compared with low‐molecular‐weight heparin. Summary: Background: There are numerous trials and several meta‐analyses comparing venous thromboembolism (VTE) prophylaxis options after total hip and knee replacement (THR and TKR). None have included simultaneous comparison of new with older options. Objective: To measure simultaneously the relative risk of VTE and hemorrhage for 12 prophylaxis options. Methods: We abstracted VTE and hemorrhage information from randomized controlled trials published between January 1990 and June 2016 comparing 12 prophylaxis options. We then constructed networks to compute the relative risk for each option, relative to once‐daily dosing with low‐molecular‐weight heparin (LMWH) Low. Results: Main : Relative to LMWH Low, direct oral Xa inhibitors had the lowest risk of total deep vein thrombosis (DVT)‐asymptomatic and symptomatic‐ (odds ratio [OR], 0.45; 95% confidence interval [CI], 0.35–0.57), translating to 53–139 fewer DVTs per 1000 patients. Vitamin K antagonists (VKAs) titrated to International Normalized Ratio [INR] 2–3 predicted 56% more DVT events (OR, 1.56; 95% CI, 1.14–2.14). Aspirin performed similarly (OR, 0.80; 95% CI, 0.34–1.86), although small numbers prohibit firm conclusions. Direct oral Xa inhibitors did not lead to significantly more bleeding (OR, 1.21; 95% CI, 0.79‐1.90). Secondary : Relative to LMWH Low, direct oral Xa inhibitors prevented 4‐fold more symptomatic DVTs (OR, 0.25; 95% CI, 0.13–0.47). Conclusions: Relative to LMWH Low, direct oral Xa inhibitors had a more favorable profile of VTE and hemorrhage risk, whereas VKAs had a less favorable profile. The profile of other agents was not more or less favorable. Clinicians should consider these profiles when selecting prophylaxis options.